Pengaruh Pemberian Ekstrak Daun Mangrove Api-api (Avicennia sp.) pada Pakan Terhadap Pertumbuhan Ikan Bandeng (Chanos chanos) - Wijianto; Fahrurrozi, Ashari (Cenderawasih University, 2023)
The aim of this research is to examine the effect of a combination of feed with api-api mangrove leaf extract (Avicennia sp.) on the growth of milkfish (Chanos chanos). One ingredient that can be used to increase fish growth is mangrove leaf extract. Mangrove leaves contain the most antibacterial compounds. This research used mangrove leaf extract Avicennia sp. which was added to the feed with 4 treatments and 3 replications. The research method used was experimental with a research duration of one month. The test results were processed using ANOVA and further tested using the Duncan Test. Based on research that has been carried out, the addition of mangrove leaf extract Avicennia sp. on feed can increase the growth of milkfish including length growth and feed efficiency with the best treatment, namely treatment B with a dose of mangrove extract of 75 ppm/500 grams of feed.